Emotional and cognitive impacts of organisational change - Daniel Wladar (Journal of Applied Leadership and Management, 2022)
Research questions: Is there a relationship between the lack of a change vision and negative emotions in the affected employees? Does insufficient communication during organisational change lead to negative emotions? Methods: Hypotheses are tested by means of quantitative primary research in the form of an employee survey at a medium-sized automotive supplier in Germany. The study is based on a questionnaire that was developed specifically for the topic of this study. The questionnaire was answered by 102 employees. Results: The analysis shows that the lack of a change vision leads to negative emotions in the affected employees. In particular, a change vision that is not perceived as desirable leads to strong negative emotions. Against the findings of the literature review, this study did not find a significant correlation between the perception of the change communication and the emotions of the change-affected employees. Structure of the article: Introduction; Literature Review; Research questions & methods; Empirical results; Conclusions; About the author; Bibliography
Keywords: 650